Pengaruh Penggunaan Aplikasi Digital AYO SRC (Sampoerna Retail Community) terhadap Peningkatan Penerimaan Toko Kelontong di Kecamatan Sokaraja - Andiana, Inggus; Arifin, Agus; Wibowo, Arif Andri (Lingka Ekonomika, 2022)
The MSME sector has an important role for the Indonesian economy and has a large share of Indonesia's GDP. One form of MSMEs is a grocery store whose existence is starting to be rivaled by modern retail stores. Sampoerna Retail Community (SRC) launched a digital application for grocery stores to compete in the digital era. The purpose of this study was to determine the effect of using the AYO SRC digital application on increasing grocery store revenue, knowing the effect of capital, store arrangement, product completeness and financial management on grocery store revenue before and after using the application and knowing the most influential variables on grocery store revenue before and after using the application. The data collection technique used an interview method based on a questionnaire, while the analysis technique used a different test and multiple linear regression. The results of this study indicate that there are differences in grocery store revenue before and after using the AYO SRC digital application in Sokaraja District. Capital and product completeness affect grocery store revenue before using the application, while after using the application the effect on revenue is capital, store arrangement and product completeness. Financial management has no effect on revenue before and after using the application. Completeness of the product is the variable that has the most influence on the revenue of the store before using the application and the arrangement of the store is the variable that affects the revenue after using the application.